2012
DOI: 10.3109/10520295.2012.672651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute treatment with dexamethasone on hemodynamic and histopathological changes in rats

Abstract: We assessed the time-dependent effects of intraperitoneal (i.p.) and intravenous (i.v.) application of dexamethasone (Dexa) on the mean arterial blood pressure (MAP), heart rate (HR) and total blood volume (TBV). We evaluated also the relation between the effects and immunoreactivities of transforming growth factor-beta (TGF-β), epithelial nitric oxide synthase (eNOS), interleukin-1 beta (IL1-β) and vascular endothelial growth factor (VEGF) in rat brain, lung and kidney tissues. Rats were anesthetized and whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In the literature there are few reports involving nitric oxide pathways and VEGF with the use of GCs. There is a study done by Ekerbiçer et al [38], in which adult mice reduced the expression of renal and pulmonary VEGF after administration of dexamethasone, also found in our study. Other authors also observed inhibition of VEGF involving the use of dexamethasone in Lewis lung carcinoma [39].…”
Section: Discussionsupporting
confidence: 87%
“…In the literature there are few reports involving nitric oxide pathways and VEGF with the use of GCs. There is a study done by Ekerbiçer et al [38], in which adult mice reduced the expression of renal and pulmonary VEGF after administration of dexamethasone, also found in our study. Other authors also observed inhibition of VEGF involving the use of dexamethasone in Lewis lung carcinoma [39].…”
Section: Discussionsupporting
confidence: 87%